Regulation of TXB2 and PGE2 production by TGF-β1 in in vitro silica dust-exposed rat alveolar macrophage - Urszula Orlinska; Douglas C. Kuhn (Mediators of Inflammation)
We investigated the effect of transforming factor factor-β1 (TGF-β1) on thromboxane B2 (TXB2) and prostaglandin E2 (PGE2) production in in vitro silica dust-exposed rat alveolar macrophages (AM). In the presence of 5 μg of anti-TGF-β1 antibodies, TXB2 production decreased, but PGE2 production increased. Addition of 2 ng of TGF-β1 to the culture medium potentiated TXB2 production, but PGE2 production apparently did not change. At 50 ng of TGF-β1, TXB2 production decreased, and PGE2 production varied. Our data suggest that in rat AM: (1) both endogenous and exogenous TGF-β1 regulate TXB2 production; and (2) in the absence of endogenous TGF-β1 the liberation of PGE2 increases; however, exogenous TGF-β1 does not have a regulatory effect on PGE2.